Case Report and Review of Keratoameloblastoma – A Rare Type of Keratin Producing Odontogenic Neoplasm (Journal of Orofacial Research, 2021)
Ameloblastoma is a slow-growing, locally invasive odontogenic tumour having odontogenic epithelial origin. Somehistological variants of ameloblastoma show keratinization such as - Acanthomatous ameloblastoma, Keratoameloblastoma andPapilliferous Keratoameloblastoma. Among these, Keratoameloblastoma is a very rare tumour. Here, we present a case ofKeratoameloblastoma in a 45-year-old female patient. Clinically, there was an extra-oral bony hard, tender swelling involvingsymphyseal and right para-symphyseal region of the mandible. Intraorally, there was a tender swelling in the dentoalveolarregion with buccal cortical plate expansion which extended from 32 to 45 tooth region. Focal area of ulceration was also seenintraorally. Based on the clinical, radiological and histopathological features, Keratoameloblastoma was diagnosed. So, eachand every case of Ameloblastoma should be judiciously examined for any histopathological metaplastic changes and also to betreated accordingly to prevent recurrence.